Jazz Analysis - Laohverapanich, Teerus (Rangsit Music Journal, 2022)
This research purpose is to present an analysis of the tunes and improvisation in 6 different styles of Jazz music including 1. New Orleans Jazz and Dixieland Jazz 2.Big Band Swing 3. Bebop 4. Cool Jazz 5. Hard Bop and 6. Modal Jazz. It focuses on explaining the analysis of jazz music with different performance and presentation methods in each style. For Selecting songs to be analyzed, the researcher uses purposive sampling by considering the widely known popular jazz music played by musicians who played a key role in the development of each of the jazz style. This research was successful in all objectives. For publishing works, the researcher took the complete research and recompiled it in the form of a monograph.